DNA mediated self-assembly of multicellular microtissues - Xiao, Mingshu; Lai, Wei; Wang, Xiwei; Qu, Xiangmeng; Li, Li; Pei, Hao (Microphysiological Systems, 2018)
Microphysiological systems (MPS) as a promising alternative can recapitulate the structure and function of native tissues in vitro, accelerating drug development and toxicity screening. DNA mediated self- assembly may encourages cell to communicate with one another and differentiates cells self-assemble into the desired microphysiological structure. Extensive studies have been conducted to construct DNA-mediated self-assembled DNA-lipid hybrid systems by integrating DNA with lipid for achieving multicellular MPS. Realization of multicellular MPS also is allowed to study physicochemical and physiological features of membrane assemblies. In addition, these arti cial DNA-lipid hybrid systems show wide applications in drug delivery, synthetic biology, and chemical process control. Herein, we present a critical review on lipid-DNA hybrid systems. After briefly introducing biophysical and biochemical characteristics of membranes, we highlight representative approaches to interact DNA with membranes, including electrostatic interactions, membrane anchors, and membrane-bound proteins. Then, we discuss the properties of DNA-functionalized membrane and factors for membrane-anchored DNA, followed by overview on applications of lipid-DNA hybrid systems in recent years. Finally, considering the great potential presented by this system, we provide insight into the outlook and challenges for future developments.